2019
DOI: 10.2105/ajph.2019.305157
|View full text |Cite
|
Sign up to set email alerts
|

Health Toll From Open Flame and Cigarette-Started Fires on Flame-Retardant Furniture in Massachusetts, 2003–2016

Abstract: Objectives. To evaluate the risk of death and injury in residential fires started on upholstered furniture, with a focus on open flame and cigarette-related heat sources. Methods. We used civilian death and injury data from 34 081 residential fires in the Massachusetts Fire Incident Reporting System from 2003 to 2016. We compared outcomes associated with fires that started on upholstered furniture ignited by smoking materials versus open flames. Results. Although fires starting on upholstered furniture were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To achieve this goal, collaboration between fire experts and toxicologists may promote a better understanding of the benefits and risks for both fire and chemical safety. 87 The authors consider that a side‐by‐side comparison for risk, such as injury, disease, or death between these two types of hazards would be beneficial to consumers and the scientific community. Collaborations among academia, government, nongovernment organizations (NGOs), and industry may lead to the use of less toxic alternative OFRs and more environmentally friendly alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, collaboration between fire experts and toxicologists may promote a better understanding of the benefits and risks for both fire and chemical safety. 87 The authors consider that a side‐by‐side comparison for risk, such as injury, disease, or death between these two types of hazards would be beneficial to consumers and the scientific community. Collaborations among academia, government, nongovernment organizations (NGOs), and industry may lead to the use of less toxic alternative OFRs and more environmentally friendly alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Fire safety scientists have questioned the efficacy of FR use in furniture, and research has shown significant health risks associated with FR exposures. Certain polybrominated diphenyl ethers (PBDEs), BDE 47 in particular, alter neurodevelopment in children, leading to decreased IQ. , They were also found to be associated with higher risk of thyroid disease among women, with stronger effects in postmenopausal women . Studies have found many halogenated organophosphate flame retardants (OPFRs) to be neurotoxic, toxic to development and reproduction, and carcinogenic .…”
Section: Introductionmentioning
confidence: 99%